Perbandingan Efektivitas Antara Metformin dan Glimepiride Berdasarkan Kadar Gdp pada Pasien Dm Tipe 2 di Rsud Dr.M.Soewandhie pada Tahun 2019 - Muhammad Zaim Abbas Hisyam; Sri Purwaningsih; Hermina Novida (Syntax Literate, 2023)
Diabetes Mellitus is a chronic metabolic disease characterized by elevated blood sugar levels and impaired carbohydrate, lipid, and protein metabolism due to betta pancreatic-cell dysfunction or insulin resistance in body cells. The prevalence of diabetes mellitus continues to increase worldwide. Indonesia itself has a prevalence of type 2 diabetes mellitus reaching 90% of all diabetes (WHO, 2016) (Riskesdas, 2018). The management of type 2 diabetes mellitus is very diverse, ranging from non-pharmacological therapy to pharmacological therapy such as insulin injection and oral anti-diabetes. Each anti-diabetic drug has a variety of ways of working, administration, and side effects. This study aims to analyze the comparison of the effectiveness of anti-diabetic medications based on blood sugar levels from the use of metformin and glimepiride (sulfonylureas) or a combination of both in patients with type 2 diabetes mellitus at Dr. Soewandhie Regional Public Hospital. This research is an analytic retrospective observational using secondary data in the form of medical records of patients with type 2 Diabetes Mellitus (outpatient) at Dr. Soewandhie Regional Public Hospital in 2019. The sample of this study consisted of 121 samples that met the inclusion criteria (43 patients on metformin therapy, 40 patients on glimepiride therapy, and 38 patients on combination therapy). The analysis of this study used data on FBG (Fasting Blood Glucose) before and three months after receiving metformin or sulfonylurea (glimepiride) therapy or a combination of both in the medical record. Data analysis of this study was performed using the Friedman test. This study showed that there was no significant difference in glycemic control (∆FBG) of metformin, glimepiride, and combination therapy in patients with type 2 diabetes mellitus (p value=0.575). There was no significant difference in the effectiveness of metformin, glimepiride, and combination therapy in patients with type 2 diabetes mellitus in Dr. Soewandhie Regional Public Hospital in 2019. In a study conducted in Japan showed that there’s efficacy of high-dose metformin use in patients with type 2 diabetes mellitus in Japan. The efficacy and safety of metformin are similar when used either twice daily or thrice daily. Further research needs to be done to assess the glycemic control (∆FBG) rate of metformin, glimepiride, and combination therapy in patients with type 2 diabetes mellitus by taking into account other factors such as medication adherence, diet, and physical activity.